The effects of tree portion on extractive content of Kelempayan (Neomalarckia cadamba sp.) wood / Nurfaizah Abd Latib, Nur Sakinah Mohamed Tamat and Jamaludin Kasim - Abd Latib, Nurfaizah; Mohamed Tamat, Nur Sakinah; Kasim, Jamaludin (2011)
The extractives provide a major contribution to the many properties of wood. Data on the extractive content of wood material is generally preferred and required for various processes and applications in the wood industry. The main objective of the study was to determine the extractive content of Kelempayan with the diameter of its breast height ranging between 35cm to 41cm. Samples were taken from each high level, namely, bottom, middle and top from three trees. The highest value of cold water was observed in the middle portion followed by the top and the bottom while the greatest value of hot water was observed in the bottom portion followed by the top and the middle. The alkali soluble content also showed a similar trend. For alcohol toluene, the highest value was observed in the bottom portion followed by the top and the middle portion.